Long-acting formulations delivering aripiprazole: beyond single-value characterizations of steady-state pharmacokinetics - McConnell SA (Dove Medical Press, 2017)
Scott A McConnell,1 Dharmik N Desai,1 Sejal P Faldu,1 Marjie L Hard,2 Angela Y Wehr,3 Peter J Weiden,1 Lisa von Moltke3 1Medical Affairs, Alkermes, Inc., Waltham, MA, 2Nuventra Pharma Sciences, Durham, NC, 3Clinical Research, Alkermes, Inc., Waltham, MA, USAThe recent publication by Salzman et al1 compared pharmacokinetic (PK) data from population PK (popPK) models for two long-acting antipsychotic formulations: aripiprazole once-monthly 400 mg (AOM 400) and aripiprazole lauroxil (AL). We would like to address a few major concerns. The AL popPK model has been well described in a peer-reviewed publication.2 However, Salzman et al omitted publishing information regarding the development and validation of the AOM popPK model, including any critical discussion of the covariates, other key characteristics, assumptions and limitations of the AOM model. Thus, a reader cannot objectively assess the simulated values for AOM reported in the publication.View the original paper by Salzman and colleagues.